PENGARUH SL-PHT TERHADAP KINERJA USAHATANI KOPI RAKYAT (Study Kasus di Kabupaten Malang dan Jombang, Jawa Timur) - Ade Supriatna (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2007)
In facing the globalization era, Indonesia as a coffee producer country took effort to increase the performance of coffee farm through the program of Integrated Pest Management-Farmer Field School (IPM-FFS). This study was conducted for five months from July throughout November 2004 in Tirtoyudo, Malang District and Wonosalam, Jombang District, East Java. The objectives of research were to evaluate the impact of IPM-Farmer Field School for coffee farms performance in aspects: of (a) the adoption of 1PM technology by farmers, (b) the farms economic visibility and (c) the farms technical efficiency. This research used the survey method and the data were analyzed by using before and after project. Primary data where collected from 80 farmers consisting of 40 IPM-Farmer Field School (alumni) and 40 non-alumni while secondary data were collected from the Office of Estate Crops, the Office of IPM Project, the Central Agency of Statistics and the Research Institutions. The results showed that after IPM-FFS, the percentage of farmers adopting IPM technology has increased as shown by the alumni (78%) and non-alumni (23%). Regular practiced field observations were able to distinguish the predators and did those who did not harm them. Most farmers applied a preventive method in controlling pest while the an-organic pesticide applied when the pests' attack reached the economic threshold. The productivity of alumni increased by 46% (1.128 to 1.641) kg/ha/year compared to that of non-alumni increased by 25% (872 to 1.087) kg/ha/year. The net income of alumni increased by 41% i.e. Rp.3.700.000,- to Rp5.200.000,- /hectare/year. Through the application of IPM technology, the farms technical efficiencies of alumni increased by 29% (0.63 to 0.81) and that of non-alumni increased by 5% (0.63 to 0.66). The program of IPM-FFS increased the performance of coffee farm, both in adoption of IPM technology, economical visibility and technical efficiency. The success of IPM-FFS program should be disseminated to other locations with some adjustments according to condition of new area. Key words: IPM-FFS, farmer, performance, coffee. Dalam menyongsong pasar bebas, Indonesia sebagai negara produsen kopi berusaha meningkatkan kinerja usahatani kopi agar mampu bersaing dengan kopi negara lain, yaitu melalui program sekolah lapang pengendalian hama terpadu (SL-PHT). Penelitian ini dilaksanakan selama lima bulan mulai bulan Juli sampai dengan Nopember 2004 di Kecamatan Tirtoyudo, Kabupaten Malang dan Kecamatan Wonosalam, Kabupaten Jombang, Jawa Timur. Tujuan penelitian adalah mengevaluasi pengaruh program SL-PHT terhadap kinerja usahatani kopi dalam aspek: (a) penerapan teknologi PHT oleh petani, (b) kelayakan ekonomi usahatani dan (c) efisiensi teknis usahatani Penelitian menggunakan metoda survei, data dianalisis secara deskriptif (sebelum dan sesudah projek). Data primer dikumpulkan dari 80 petani terdiri atas 40 petani alumni SL-PHT dan 40 petani non-alumni, sedangkan data sekunder diperoleh dari Dinas Perkebunan, Kantor Projek PHT, Badan Pusat Statistik, dan Lembaga Penelitian. Hasil penelitian menunjukan bahwa setelah SL-PHT, persentase petani yang mengadopsi teknologi PHT meningkat, petani alumni (78%) dan non-alumni (23%) sudah menerapkan pengamatan agro-ekosistem kebun secara berkala, memahami keberadaan musuh alami dan melestarikannya. Dalam mengendalikan hama, sebagian besar petani menerapkan cara pencegahan (preventive controls), Pestisida an-organik akan diaplikasikan apabila gangguan hama sudah mencapai tingkat ambang ekonomi. Produktivitas kopi petani alumni meningkat 46% (1.128 menjadi 1.641) dan non-alumni meningkat 25% (872 menjadi 1.087) kg/ha/tahun. Pendapatan bersih petani alumni meningkat 41% (Rp.3,7 menjadi Rp.5,2) juta/ha/tahun. Efisiensi teknis usahatani petani alumni meningkat 29% (0,63 menjadi 0,81) dan non-alumni meningkat 5% (0,63 menjadi 0,66). Program SL-PHT dapat meningkatkan kinerja usahatani kopi, baik aspek penerapan teknologi PHT, kelayakan usahatani maupun efisiensi teknis. Keberhasilan program SL-PHT dapat didesiminasikan ke lokasi-lokasi lain dengan penyesuaian berdasarkan kondisi lokasi baru.Kata kunci: SL-PHT, petani, kinerja, kopi.